2019
DOI: 10.7567/1347-4065/ab12cb
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of temperature dependence of sound velocity in biological tissues

Abstract: Transcatheter arterial chemo-embolization using Lipiodol ® is one of the treatments for hepatocellular carcinoma. During this procedure, it is important to monitor the Lipiodol ® deposited inside tumors. This study proposes a method for measurement of the temperature dependence of the velocity of sound in biological tissues. An ultrasonic pulse-echo method was used to measure the velocity of sound. The temperature coefficients of the velocity of sound for Lipiodol ® was −2.82 m s −1 °C−1 . Values of 1.07 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In the previous study, the temperature coefficient of the sound velocity of Lipiodol showed negative values and that of rat liver tumor showed positive values [ 23 ]. Therefore, that of rat liver tumor injected with Lipiodol can show various values from negative to positive values depending on the degree of Lipiodol, which can reflect the amount of Lipiodol filled in the liver tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, the temperature coefficient of the sound velocity of Lipiodol showed negative values and that of rat liver tumor showed positive values [ 23 ]. Therefore, that of rat liver tumor injected with Lipiodol can show various values from negative to positive values depending on the degree of Lipiodol, which can reflect the amount of Lipiodol filled in the liver tumor.…”
Section: Discussionmentioning
confidence: 99%
“…This method has the potential to facilitate the in vivo evaluation of the volumetric distribution of Lipiodol inside tumors, since Lipiodol primarily consists of poppy-seed oil. A previous in vitro study demonstrated that tumors implanted in a rat liver and Lipiodol had different temperature coefficients of the sound velocity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the fat content of tissue can be characterized by measuring the change in sound velocity that occurs when biological tissue is heated non-invasively with ultrasonic waves [13]. Measurements of the rate of change in sound velocity between normal livers and those affected by hepatocellular carcinoma (HCC) in rats were 1:07 AE 0:02 m/s/ C and 1:59 AE 0:04 m/s/ C, respectively [15]. These results suggest the possibility of NASH diagnosis using thermophysical properties.…”
Section: Ultrasonic Diagnosis Of Liver Cancermentioning
confidence: 99%
“…Ultrasonic absorption is determined by the viscosity of a propagation medium. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The viscosity can be classified into two types based on the deformation mode of the medium: the shear and volume viscosities. Many types of ultrasonic relaxation in aqueous solutions of ionic salts occur through the modification of temperature, which is the direct contribution of adiabatic volume compression.…”
Section: Introductionmentioning
confidence: 99%